2003
DOI: 10.1021/jm034111v
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Substitution Can Block CYP3A4 Metabolism-Dependent Inhibition:  Identification of (S)-N-[1-(4-Fluoro-3- morpholin-4-ylphenyl)ethyl]-3- (4-fluorophenyl)acrylamide as an Orally Bioavailable KCNQ2 Opener Devoid of CYP3A4 Metabolism-Dependent Inhibition

Abstract: The formation of a reactive intermediate was found to be responsible for CYP3A4 metabolism-dependent inhibition (MDI) observed with (S)-N-[1-(3-morpholin-4-ylphenyl)ethyl]-3-phenyl-acrylamide (1). Structure-3A4 MDI relationship studies culminated in the discovery of a difluoro analogue, (S)-N-[1-(4-fluoro-3-morpholin-4-ylphenyl)ethyl]-3-(4-fluoro-phenyl)acrylamide (2), as an orally bioavailable KCNQ2 opener free of CYP3A4 MDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…Pharmacophore, tree models, and the logistic regression model were tested with molecules outside of the training set using recently published data for 12 compounds (Yamazaki and Shimada, 1998;Kasahara et al, 2000;Kim et al, 2001;Kajita et al, 2002;Chatterjee and Franklin, 2003;Wu et al, 2003) with MIC formation for CYP3A4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacophore, tree models, and the logistic regression model were tested with molecules outside of the training set using recently published data for 12 compounds (Yamazaki and Shimada, 1998;Kasahara et al, 2000;Kim et al, 2001;Kajita et al, 2002;Chatterjee and Franklin, 2003;Wu et al, 2003) with MIC formation for CYP3A4.…”
Section: Methodsmentioning
confidence: 99%
“…This type of screen is useful for identifying potential inhibition of coadministered drugs and is commonly followed by time-dependent inhibition studies (Wu et al, 2003). These studies may be supplemented with additional in vitro assays with more traditional drug substrate probes using liquid chromatography/mass spectrometry analysis (Ekins et al, 2000b).…”
mentioning
confidence: 99%
“…For example compound (95) with its benzo-[1,3]dioxole ring system had an EC 50 value of 6 nM while compound (96) containing the larger dihydro-2H-benzo- [1,4]oxazine system was also very potent with an EC 50 value of 9 nM. Addition of a fluorine at the R3 position was tolerated and was later reported to be beneficial from a metabolism standpoint [103]. Further chemistry indicated that the addition of a hydroxyl functionality to the terminus of themethyl group (compounds 99-101, Table 12) was tolerated [104].…”
Section: Cinnamide Derivatives and Analoguesmentioning
confidence: 99%
“…3). Structure-metabolism dependent inhibition (MDI) relationship studies resulted in the discovery of a difluoro analog of 1 (4) as an orally bioavailable KCNQ2 opener free of CYP3A4 MDI [79]. Another example where metabolite identification at early stages helped the chemists with the design of a safer drug candidate included the discovery of a potent and selective cycloxygenase-2 inhibitor, L-768,277 [80].…”
Section: Mass Spectrometry In Studies Of Drug Biotransformation (Metamentioning
confidence: 99%